Mutation Materialized: The Concept as Method - Stilgren, Rosa (Journal of Posthumanism, 2024)
Concepts have been disregarded from posthuman studies as static entities that constitute and reinforce anthropocentric categories. This article explores how concepts can be used as methods, investigating the intersection between posthuman theories, media studies and algorithmic audio production. Following Mieke Bal’s framework of concept-based methodology (Bal, 2009) as source of inspiration, this paper explores how concepts work as socio-material entities to analyze specific arrangements, exploiting the concept’s multiplicity (Deleuze & Guattari, 1994) defining the concept as an agent that “works” (Slaby et al., 2019). Thereby acknowledging that the concept itself will not be unaffected by process of analysis. The article focuses on the concept of mutation as an autonomous process of being and becoming that identifies specific transformations in digital audio production, illuminating the interplay between concept-ualization as normative systems of being and concept-ing (Taylor et al., 2023) as active processes of becoming.